ANALYSIS OF OPTIMALITY CRITERIA FOR THE DRILLING PROCESS OF OIL AND GAS WELLS WITH PDC BIT TYPE - Зварич, Галина (SWorldJournal, 2025)
The paper considers the issue of increasing the efficiency of the drilling process of oil and gas wells using PDC bits. The main optimality criteria that determine the quality and efficiency of the drilling process are analyzed, in particular: mechanical